Vitamin D deficiency may stimulate fibroblasts in Dupuytren's disease via mitochondrial increased reactive oxygen species through upregulating transforming growth factor-β1. (July 2018) - Seyhan, Harun; Stromps, Jan-Phillip; Demir, Erhan; Fuchs, Paul C.; Kopp, Jürgen
Abstract: Dupuytren's disease, a benign fibroproliferative disorder of the palmar fascia, represents an ideal model to study tissue fibrosis. Transforming growth factor-β1 (TGF-β1) and its downstream Smad signaling system is well established as a keyplayer during fibrogenesis. Vitamin D has been extensively studied as an anti-fibrotic agent in malignant chronic diseases. A number of studies have shown that myofibroblasts are main target cells of 1, 25(OH)2 D3 inhibitory action. The myofibroblast in the palmar aponeurosis of patients in different stages of Dupuytren's disease was found by electron microscopy to contain a large number of mitochondria. Mitochondria play a critical role in cell metabolism being the major source of reactive oxygen species (ROS) in cells. TGF-β1 has been shown to increase mitochondrial ROS production in different cell types, which mediate fibrosis related gene expression and myofibroblast differentiation. TGF-β1 increases mitochondrial ROS production in patients with Dupuytren's contracture potentially in consequence of Vitamin D deficiency, leading to myofibroblast differentiation. Thus, targeting this basic pathomechanism seems suitable to establish new treatment strategies.